Ser español en el ballet académico : estereotipo de una identidad sin escuela nacional - Patricia Bonnin-Arias et Juan Arturo Rubio Arostegui (Amnis)
National reception of academic ballet in Spain is constrained by its institutional context. Stakeholders of the Spanish choreographic field of academic ballet (masters, choreographers, performers) define distinctly a form of being, of doing and of attitude of the stereotyped Spanish dancer in comparison with the foreign. This is despite the fact that in Spain a national school of academic ballet has not been institutionalized as a result of a weak and ineffective cultural policy throughout its history.